Game representation - code form - Matos, M. C. P.; Ferreira, M. A. M. (The Complex Networks of Economic Interactions: Essays in Agent-Based Economics and Econophysics, 2006)
When we analyze a game we want a full representation, i.e., we want to be able to look at a game and perceive all of its details. If it allows us to visualize the respective solution all the better. This aim was the reason for researching a new game representation which is described in this paper. The code form of a game consists mainly in a table containing all of the information with no suppression or “adulteration” with regards to the game. Initially presented at Fifth Spanish Meeting on Game Theory & European Voting Games (Seville 2002), based on examples, code form is put forth in this paper thoroughly. We begin by presenting code form, exemplifying it with four games. We finish proving the existence of Nash Equilibrium in code form games.